1996
DOI: 10.1111/j.1574-6968.1996.tb08477.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of a dextranase-encoding cDNA from Penicillium minioluteum

Abstract: A cDNA from Penicillium minioluteum HI-4 encoding a dextranase (1,6-a-glucan hydrolase, EC 3.2.1 .l 1) was isolated and characterized. cDNA clones corresponding to genes expressed in dextran-induced cultures were identified by differential hybridization. Southern hybridization and restriction mapping analysis of selected clones revealed four different groups of cDNAs. The dextranase cDNA was identified after expressing a cDNA fragment from each of the isolated groups of cDNA clones in the Escherichia coli T7 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…In fraction rK 15 of the recombinant protein digest ( Fig. 1B), an unexpected peptide with m/z 3231.7 was observed.…”
Section: Protein Sequence Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…In fraction rK 15 of the recombinant protein digest ( Fig. 1B), an unexpected peptide with m/z 3231.7 was observed.…”
Section: Protein Sequence Analysismentioning
confidence: 98%
“…Natural K-1,6 glucan-6-glucanohydrolase was puri¢ed from the culture ¢ltrate of a P. minioluteum Hl-4 strain supplied by the Center for Genetic Engineering and Biotechnology (La Havana, Cuba). The recombinant enzyme was obtained by cloning of the DEX gene from P. minioluteum in the methylotrophic yeast P. pastoris under the control of the AOX promoter using the SUC2 gene signal sequence from S. cerevisiae [15].…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asp353, Glu356, Asp372, Asp373, and Trp402, whose substitutions resulted in the reduction of the activity for both pullulan and panose, were predicted to be located in potential subsites )1 and )2 (a detailed description is given in the next section). Trp31 and Glu273, whose [12]; DEX49A, Penicillium minioluteum dextranase isoform [13]; PFDEXA, Penicillium funiculosum dextranase (DDBJ/EMBL/GenBank No. AJ272066); AGTDEX1 and 2, Arthrobacter globiformis T-3044 endodextranase 1 and 2 [14]; AGCDEX, Arthrobacter sp.…”
Section: Properties Of Asp-and Glu-mutated Enzymesmentioning
confidence: 99%
“…Interestingly, IPU does not hydrolyse dextran at all, while all other GH family 49 enzymes are dextran-hydrolysing enzymes, such as endo-dextranase (EC 3.2.1.11) [11][12][13][14] and isomaltotrio-dextranase (EC 3.2.1.95) [15]. We have reported the molecular cloning of IPU, and indicated that seven highly conserved regions are found among the primary structures of these dextran-hydrolases and IPU [2].…”
mentioning
confidence: 99%